2020
DOI: 10.1177/1545968320916159
|View full text |Cite
|
Sign up to set email alerts
|

Is Symptomatic Fatigue Associated With Physical Activity and Sedentary Behaviors Among Persons With Multiple Sclerosis?

Abstract: Background. Fatigue is a debilitating symptom in multiple sclerosis (MS) that may be associated with reduced physical activity and increased sedentary behavior. Objective. This study examined the associations among fatigue and device-measured physical activity and sedentary behavior in people with MS. Methods. The participants (n = 252) completed the Patient Determined Disease Steps (PDDS) and Fatigue Severity Scale (FSS) and wore a waist-mounted accelerometer for 7 days. Participants were divided into 2 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…In terms of PA intensity, the percentages of SB (63 to 68% for men and women respectively) and LPA (20 to 27%) here calculated, were found fully consistent with those reported in previous studies which indicated values from 60 to 70% for SB and 27 to 37% for LPA [16,[42][43][44]55]. In contrast, the percentage of time spent in MVPA (approximately 10%), was found slightly higher than what usually observed for pwMS (1-7%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of PA intensity, the percentages of SB (63 to 68% for men and women respectively) and LPA (20 to 27%) here calculated, were found fully consistent with those reported in previous studies which indicated values from 60 to 70% for SB and 27 to 37% for LPA [16,[42][43][44]55]. In contrast, the percentage of time spent in MVPA (approximately 10%), was found slightly higher than what usually observed for pwMS (1-7%).…”
Section: Discussionsupporting
confidence: 91%
“…Although the level of disability and duration of the disease were similar across men and women of our sample, it is to be considered that men usually take less time than women to reach the same impairment level, and thus that the trajectory of change in attitude to performing PA may be different for the two sexes. In this context, the results which refer to sedentariness should be further verified in future studies performed on larger cohorts, as there are factors (like for example fatigue, but also the presence of specific disabilities which affects mobility [55]) that are likely to change with the duration of the disease, thus also modifying the propensity to perform PA.…”
Section: Discussionmentioning
confidence: 89%
“…Although there is a body of knowledge on the association between fatigue and PA, the complex relationship between these factors and gender is limited. Moreover, although there is little known about the relationship between fatigue and PA levels in patients who have recovered from COVID-19, studies have revealed the nature of this relationship in several disease populations [19][20][21]. Clinical data regarding COVID-19 point towards gender-based differences in COVID-19 severity [22].…”
Section: Introductionmentioning
confidence: 99%
“…In MS, studies evaluating physical activity using commercial wearables have shown (1) strong-moderate correlations between clinical and patient-reported disability measures ( 6 , 74 80 ), (2) continuous observation provides less biased assessment vs. sporadic cross-sectional measures ( 6 , 74 , 81 , 82 ), (3) fatigue is not the only factor affecting sedentary behavior and physical activity in MS ( 83 , 84 ) and (4) that average daily step count (STEPS) is responsive to change over 1-year, even when conventional measures remain stable ( 74 ).…”
Section: Remote Evaluation Of Fatigue and Fatigabilitymentioning
confidence: 99%